Intelligence activities in the records of the dynastic chronicler Idris Bidlisi - Gačanin, Sabaheta (Historical Thought, 2024)
While reading Idrīs Bidlīsī’s chronicle, we find records of spies’ activities in many places, either through direct references or indirect ones, as an element of the war strategy of the Ottoman state. This article uses philological methods to investigate the records of the intelligence activity of the Ottoman state in the imperial expansion, which we find in the dynastic chronicle of Idrīs Bidlīsī, as well as those in the reports of Bidlīsī as a participant in the east of the Empire during the conflict between the Ottoman Empire and the Safavids. The dynastic chronicle dates to the first decade of the 1500s, and although with meager data, is a valuable historical source that gives a view of the work and contribution of spy networks in the military-political strategy of the Ottoman imperial policy. Bidlīsī’s letters as reports are complementary sources to Bidlīsī’s chronicle.